Utilization Rate of Bronchoscope in Tertiary Care Hospital: An Evaluation from the Perspective of Operational Management - Mahwish Suhaib; Pradeep Srivastava; Nitin D Bhardwaj; Seema Khan; Anmol Jain; Saumya Rawat (Indian Journal of Respiratory Care)
Introduction: A bronchoscope is important medical equipment used for bronchoscopy, a procedure that allows visualization of the upper and lower respiratory tract. Utilization of equipment is an important aspect for optimal patient handling and quality of care. The utilization coefficient (UC) gives a picture of the level of utilization of the equipment, which can be optimally utilized, overutilized, or underutilized. Materials and methods: A descriptive study was conducted in the respiratory medicine department of a tertiary care government teaching hospital for one month. The UC of the bronchoscope was calculated, taking into consideration the maximum hours it can be used in a day and the average hours it is used each day. Results: The average time the bronchoscope is used per day came out to be 4 hours, and the maximum time the bronchoscope can be used per day is 5 hours. The UC came out to be 80%, thus indicating optimal utilization of the bronchoscope. Conclusion: Results cater attention toward optimal utilization of equipment, which is an important factor frequently overlooked by management in the healthcare delivery system and can lead to losses by reducing yield.